Impact of arteriovenous fistulas versus arteriovenous grafts on vascular access performance in haemodialysis patients: A systematic review and meta-analysis. (December 2022) - Hajibandeh, Shahin; Burton, Hannah; Gleed, Philippa; Hajibandeh, Shahab; Wilmink, Teun
Background: Controversy exists regarding the best-performing vascular access type for patients undergoing haemodialysis. We aimed to compare outcomes of starting dialysis on arteriovenous fistulas (AVFs) versus arteriovenous grafts (AVGs) in haemodialysis patients. Methods: We conducted a systematic search of multiple electronic information sources and bibliographic reference lists. The following outcome parameters were evaluated at 1, 2 and 5 years: primary failure, defined as access never used for dialysis; primary patency, defined as intervention-free access survival; primary-assisted patency, defined as uninterrupted access survival with interventions; and secondary patency, defined as cumulative access survival. Results: We identified 15 comparative studies reporting a total of 118, 434 patients who initiated haemodialysis with AVF ( n = 95, 143) or AVG ( n = 23, 291). Our analysis demonstrated that AVF was associated with significantly higher primary failure rate (OR: 2.05, p = .0005) but significantly higher rate of primary patency at 1 year (OR: 1.91, p < .00001), at 2 years (OR: 2.52, p < .00001) and at 5 years (OR: 2.59, p < .00001); and primary-assisted patency at 1 year (OR: 1.71, p < .00001), at 2 years (OR: 2.13, p < .00001) and 5 years (OR: 2.79, p < .00001). There was no significant difference in secondary patency at 1 year (OR: 1.08, p < .00001) but AVF had better secondary patency at 2 years (OR: 1.26, p < .00001) and 5 years (OR: 1.60, p < .00001) than AVG. Conclusions: The meta-analysis of best available comparative evidence (Level 2) demonstrated that AVFs may be associated with significantly higher primary failure rate but higher primary patency, primary-assisted patency and secondary patency at 1, 2 and 5 years compared to AVGs. However, the available evidence is subject to significant selection bias and confounding by indication.